2022
DOI: 10.3390/ijms24010204
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Natural Killer Cell Innate Immunity against Hematologic Malignancies: From Stem Cell Transplant to Adoptive Transfer and Beyond

Abstract: Numerous recent advancements in T-cell based immunotherapies have revolutionized the treatment of hematologic malignancies. In the race towards the first approved allogeneic cellular therapy product, there is growing interest in utilizing natural killer (NK) cells as a platform for off-the-shelf cellular therapies due to their scalable manufacturing potential, potent anti-tumor efficacy, and superior safety profile. Allogeneic NK cell therapies are now being actively explored in the setting of hematopoietic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…NK-92 cells exhibit potent cytotoxicity against several cancer cells, a phenomenon primarily ascribed to the overexpression of numerous activating receptors, concurrent downregulation of almost all inhibitory receptors, and heightened expression of perforin and granzyme. Furthermore, NK-92 cells can continuously proliferate with a doubling time of 2–4 days, are easily obtainable, and have a homogeneous phenotype [ 163 , 164 ]. However, due to their cancerous nature, NK-92 cells must be mitotically inactivated prior to infusion into patients to inhibit undesired clonal proliferation, which restricts their persistence and expansion in vivo, and allogeneic administration demands very high doses of NK-92 cells [ 165 ].…”
Section: Nk Cell Immunotherapy In Nhlsmentioning
confidence: 99%
See 1 more Smart Citation
“…NK-92 cells exhibit potent cytotoxicity against several cancer cells, a phenomenon primarily ascribed to the overexpression of numerous activating receptors, concurrent downregulation of almost all inhibitory receptors, and heightened expression of perforin and granzyme. Furthermore, NK-92 cells can continuously proliferate with a doubling time of 2–4 days, are easily obtainable, and have a homogeneous phenotype [ 163 , 164 ]. However, due to their cancerous nature, NK-92 cells must be mitotically inactivated prior to infusion into patients to inhibit undesired clonal proliferation, which restricts their persistence and expansion in vivo, and allogeneic administration demands very high doses of NK-92 cells [ 165 ].…”
Section: Nk Cell Immunotherapy In Nhlsmentioning
confidence: 99%
“…Furthermore, preclinical data indicated that the combination of haNK cells withmAbs, such as daratumumab for multiple myeloma (MM) and rituximab for NHL, may have a synergistic effect. However, further clinical investigation is required to validate these approaches for NHL [ 163 ].…”
Section: Nk Cell Immunotherapy In Nhlsmentioning
confidence: 99%